O brincar na educação infantil com base em atividades sociais, por um currículo não encapsulado - Teles, Fabricia Pereira (2018)
This doctorate dissertation, in general, investigates play in the reorganization of the curriculum of a school of early childhood education, located in the city of Parnaíba-PI, before and during the development of a project organized based on social activities (LIBERALI, 2009, 2012, 2015). The research discusses the development of teachers and children’s new ways of acting at school, based on early childhood education central concepts and actions, addressing, in a central way, the play and the social activities in which the children participate, and in this context, approppriate of their culture, take positions and become agents (STETSENKO; HO 2015). The Social Activities curriculum enables teachers and children to grasp historically produced knowledge, as well as new ways of acting that (re) signify life in school and in society. In view of this, two main axes are basic to the theoretical and theoretical-methodological discussion of this essay: playing in the curriculum of early childhood education and the proposal of curricular reorganization through social activities. The discussions about the concept of curriculum are based on Apple (1982), Sacristán and Pérez Gómez (1998), Silva (2011), Kuhlmann Jr (2003), Kramer (2014) Oliveira (2010, 2015), Barbosa and Horn (2008), Barbosa et al. (2016). The concept of play considers the references of Brougère (1998, 2003) and Kishimoto (1994, 1996) to the dialogue centered on the theories of Vigotski (1933/2007), Elkonin (1978/2009) and discussions of Newman and Holzman (2014), Stetsenko (2015, 2016), among others of vigotskiana base. The first axis focuses on the curriculum in relation to the conceptions and values present in the models of practices adopted at school about play in childhood. The second proposal is to overcome a traditional curriculum based in early childhood education presenting a new proposal based on social activities, supported by the assumptions of Socio-Historical-Cultural Theory (VIGOTSKI, 1930/2004, 1934/2007, LEONTIEV, 1972/2004, ENGESTRÖM, 2002, 2013, among others. This study - inserted in the area of Applied Linguistics, which understands language as implicated in social life (MOITA LOPES, 2006), specifically in the school life of adults and children - has the methodological choice of Critical Collaboration Research because it understands the research as an intentional process of understanding and transformation, organized by the contradiction and collaboration movements, which focus on the creation of proximal development zones (VIGOTSKI, 1930/2007). The research data, produced at training meetings, planning, classes and performances (jokes), photographs and videos were analyzed based on the argumentative perspective of language (LIBERALI, 2013) articulated to multimodality (KRESS, 2010). In an attempt to explain and understand the organization and movement of the activity of play, both before and during the project by social activities, the analyzes revealed that the implementation of the project at the Parnaíba-PI early childhood institution provided new ways of acting, conceiving and living the play by adults and children. These aspects guided the transformation of educational practices, made possible by the new understandings about the right to play in school, not as a leisure, but as an important element for purposes of teaching-learningdevelopment with primordial relevance to the respect of childhood. The transformations subsidized, afterwards, the strengthening of the curricular proposal of the institution, context of the research